Ambivalence in Place Attachment: The Lived Experiences of Residents in Declining Neighbourhoods Facing Demolition in Shenyang, China - Xin Li; Reinout Kleinhans; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
This paper investigates the place attachment of residents in declining neighbourhoods that are facing demolition in Shenyang, China. Through in-depth interviews with homeowners living in danwei communities, or urban villages, at the pre-demolition phase, this paper reveals the strong connection between place attachment and both positive and negative lived experiences. The homeowners cleverly mobilise stable neighbourhood features and the challenges brought by neighbourhood changes to relieve their life constrains, such as the form of dwellings, low living costs and the place identity, which contributes to the development of place attachment. However, various forms of neighbourhood decline have negative effects on their place attachment. Urban redevelopment, therefore, confronts residents with a dilemma concerning the relative importance of their sense of rootedness in the neighbourhood and the desire to relocate to achieve better living conditions. By exploring this ambivalence, this paper displays how neighbourhood decline, and the impending demolition, affect residents' lived experiences and how residents in turn reconstruct their place attachment.
Keywords: O18; R23; 330; place attachment; ambivalence; lived experiences; declining neighbourhoods; urban redevelopment; China